Sequential Copper-Catalyzed Amidation and Hydroxylation for Acetaminophen Synthesis - Seo, Youngran; Yoo, Dongwon; Kim, Young Gyu (Synlett, 2024)
A sequential Cu-catalyzed amidation and hydroxylation of p-dihalobenzenes is applied to synthesize acetaminophen. This method allows the direct introduction of acetamido and hydroxy groups under acid-free conditions without forming other regioisomers. By using a one-pot process, acetaminophen can be prepared with an overall yield of up to 74%.
Keywords: acetaminophen; paracetamol; amidation; hydroxylation; copper catalysis